Dysadaptation mechanisms of the human’s in Antarctic - Moiseyenko, E. V. (Ukrainian Antarctic Journal, 2009)
Long-term complex monitoring medical-biological researches of the human’s functional systems status at the prolonged stay in the conditions of isolation at the off-shore (coast) Antarctic station were focused on finding out of mechanisms of dysadaptative disorders development of integrative and oxygen-transport systems of organism in the absence of essential reduction of the oxygen content in atmospheric air. Work was based on the results of medical-biological studies, which were conducted with participation of the crew members of the Antarctic station Academician Vernadskiy (Vernadsky – 65° 14’43"S; 64° 15’24"W). The average age of examinees was 39,8±2,4 years (130 men). The medical-biological studies included the modern clinic-laboratory, functional, instrumental, biochemical, immunologic, genetic, statistical methods. The participants’ examinations of the expedition were conducted before expedition, at a period of transatlantic transition, on Antarctic station (in mode of the monitoring by means of telemedical connection), after returning from expedition. In Antarctic the unique complex of physical, chemical, biological, of social, nature (the metheoheliogeophysical, biorhythmological, deprivation) factors, exceeding by power and duration, affect a human. Long influence of these factors brings to the adaptation processes disorders and dysadaptative development. It is shown that the mechanisms of dysadaptative disorders of oxygen-transport systems of the human organism at the long stay under the influence of the complex of extreme factors of Antarctic expedition developed on the background of the chain neurohumoural, neuroimmune, metabolic, celluar dysfunctions, which indicated on the presence of signs of long stressful condition (the stress-syndrome) that brings to adaptative mechanisms exhaustion of compensation and requires using the methods of correction. At the long stay of a human on the coast Antarctic station, there was revealed the seasonal dynamics of adaptative-dysadaptative rebuildings of regulative and oxygen-transport systems, there was revealed the presence of signs of stressful status and development of tissue hypoxia. It was shown the pathogenic mechanisms of development of dysadaptative disorders of integrative systems (change in cerebral electrogenesis, the activation of sympathoadrenal system, immune malresistance), respiratory, circulatory and hemic mechanisms of regulation of organism oxygen modes (the fall in efficiency and economy of the regulation mechanisms). It is shown the role of biorhythmologic and heliophysical factors of environment in development of dysadaptative disorders. It is for the first time fullfilled the genetic typization of the participants of Antarctic expedition on the presence of an allele polymorphism of specific genetic factor (hypoxia inducted factor - HIF-1α). The significance of such human gene HIF-1α polymorphism is studied in correction to development of adaptative-dysadaptative rebuildings of the functional systems at a continuous stay in Antarctic. It is shown the stabile reduction of regulation mechanisms of an organism oxygen modes under influence of Antarctic factors and hypoxia loading among winterers with C/T polymorphism of the gene HIF-1α, that has prognostic importance and opens way to deepened study of the molecular mechanisms role in development adaptative-dysadaptative processes in a human in extreme conditions.